Appalili and Katto Bokko Agrarian Rites of the Indigenous People of Kekaraengan Marusu in Maros Regency - Muhammad Azhar Husnan; Alya Daniyah Rosyadah; Andi Usrawi Mappaseng (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2026)
This research will examine the existence, changes, and social impacts of two agrarian rites belonging to the Kekaraengan Marusu Indigenous People in the Kassi Kebo Environment, Bajubodoa Village, Maros Baru District, Maros Regency. Namely the Appalili rite, as a marker of the rice planting season and the Katto Bokko rite as a marker of the harvest season. Motivated by the threat of the sustainability of these two rites in line with the shift in the economic structure of Maros Regency from the agricultural sector to the increasingly massive transportation, warehousing, and processing industry sectors, as stated in the "Maros Regency RPJPD 2025-2045". The objectives of the research include: (1) tracing the existence and background of the Appalili and Katto Bokko agrarian rites; (2) track changes in both rites historically from the time span in 2000 to 2025; and (3) the impact of the rite on the community, especially regarding social interaction and food security of indigenous peoples in the Kassi Kebo Environment. The research uses a multi-method qualitative approach with primary data sources through observation, interviews, documentation, and secondary data sources through literature search. The theoretical approach or framework used in this study belongs to Émile Durkheim, James C. Scott and Giorgio Agamben. Then it was analyzed using triangulation methods and data. The results of the study show that: (1) The Appalili Rite has been present since the 16th century through the discovery of pajekko (sacred plow tools) during the 6th Karaeng Marusu period, along with the existence of Katto Bokko; (2) Changes that have occurred since 2000 include the loss of the role of pappananrang as an expert in determining time or "good days" based on the reading of constellations, weather and climate. There are also in terms of heirloom materials and the involvement of the Regional Government since 2014; (3) How the two rites have proven to serve to strengthen social solidarity, as well as a means of preserving local agricultural biodiversity through the management of bandaq and punuq rice varieties as the backbone of community food security.